Le fratture-lussazioni della Lisfranc - Di Bisceglie, F.; Mugnaini, M.; Bardelli, M. (Lo Scalpello - Journal, 2018)
LISFRANC FRACTURE-DISLOCATIONSLisfranc fracture-dislocations are an uncommon injury involving the tarsometatarsal joint and represent a broadspectrum of injuries, which can be purely ligamentous or may involve the osseous and articular structures. Lisfrancinjuries are often misdiagnosed and mismanaged; if they are not detected at an early stage and appropriately treated,they can cause long-term disability and will lead to midfoot arthritis. This article outlines the anatomy, epidemiology,classification, investigation and current evidence on treatment of this injury.